Effects of feral horse herds on plant communities across a precipitation gradient - Baur, Lauren, author; Smith, Melinda D., advisor; Schoenecker, Kathryn A., committee member; Meiman, Paul, committee member (Colorado State University. Libraries, 2016)
Feral horse herds in the western United States are managed with the goal of maintaining "a thriving natural ecological balance" with their environment. Because rangeland ecology is complex and grazers such as horses can have different effects under different environmental conditions, more data are needed to better inform Appropriate Management Levels and other management decisions. We used long-term grazing exclosures and fenceline contrasts to evaluate the impacts of feral horses on plant communities at five sites across the western United States. These sites ranged from 229 to 413 mm mean annual precipitation and represented four different ecosystems (Great Basin desert, Colorado Plateau, Rocky Mountain grassland and mixed grass prairie). We found that feral horses significantly reduced grass biomass and total biomass at alpha=0.1, but did not have a significant effect on plant community composition, species richness, diversity, evenness, or dominance. The effects of horses did not vary by site, indicating that different precipitation levels are not driving differences in grazing effects within the range encompassed by our sites. In other words, our results imply that while feral horses do reduce plant biomass, they are not causing plant community shifts, and their effects may not be as site-specific as has been assumed. Additional multi-site studies, preferably with standardized exclosures and larger sample sizes, would increase our understanding of feral horse grazing effects.